Pendampingan Kewirausahaan Pembuatan Baju Dan Bross Di Lembaga Kesejahteraan Sosial Anak Panti Asuhan “Al-Amin” Kedungturi Sidoarjo - Sutono; Ach Khusnan (PUDAK: Local Wisdom Community Journal, 2023)
The aim of mentoring is an effort to form an entrepreneurial mentality for children in orphanages. Apart from that, this activity can also get a good response from the community, so that all the products produced by children in foster care can be accepted at several institutions including schools and Islamic boarding schools. However, due to their lack of knowledge and experience, their clothes and brooch sewing business has failed. This assistance is based on the problem of how to provide entrepreneurship assistance to children in the LKSA Al-amin dormitory and what must be done to form children's independence in the practice of making clothes and brooches. To explore these problems, the researcher used a qualitative descriptive method by collecting data using observation, interviews and documentation, as well as data analysis and data validity using data triangulation. Assistance efforts in making clothes and brooches are a concrete form of the process of strengthening soft skills in children. As productive young people, those in orphanages have the potential to develop better in order to create economic independence within themselves. Apart from that, this program also aims to create independent young entrepreneurs who are able to create business opportunities for orphanages and the surrounding community. The results achieved in this mentoring program for the community are making creatively designed stitches and unique shirts, increasing children's resources so they are able to produce, and can have implications for meeting children's needs.